Intensity-modulated radiation therapy of anal squamous cell carcinoma: Relationship between delineation quality and regional recurrence. (February 2019) - Rouard, Nathalie; Peiffert, Didier; Rio, Emmanuel; Mahé, Marc-André; Delpon, Gregory; Marchesi, Vincent; Falk, Alexander T.; Salleron, Julia; Serre, Anne-Agathe
Abstract: Background and purpose: Intensity-modulated radiation therapy (IMRT) is currently indicated to treat anal squamous cell carcinoma (ASCC). Conformal dose delivery and steep dose gradients may cause marginal misses. We analyzed patterns of locoregional recurrences (LRR) and delineation quality to determine IMRT-specific predictive factors. Material and methods: Lymph node area delineation was classified as "compliant" or "non-compliant" according to experts' workgroup recommendations. The recurrence volume (Vrecur ) was delineated on initial planning-CT by recurrence imaging registration. The Vrecur was determined to be "in-field" (IF), "marginal" (ML), or "out-of-field" (OF) in regard to the 95% isodose coverage. Results: Out of 165 patients, 30 had LRR. Among the 27 local recurrences (LR), 20 (74%) were IF, 4 (15%) ML, and 2 (7%) OF. Fourteen patients had regional recurrence (RR), amounted to 33 separate recurrence sites (RS). RS were mostly localized in inguinal ( n  = 12;36, 4%), external iliac ( n  = 7;21.1%), presacral ( n  = 4;12.1%) and common iliac ( n  = 3;9.1%) nodes . Eighteen (54.5%) RS were IF, 6 (18.2%) ML, and 9 (27.3%) OF. Performance status ≥2 ( p  = 0.007) and active smoking ( p  = 0.025) were predictors of LR. Immunodepression ( p  = 0.012), external iliac involvement ( p  < 0.001), and non-compliant delineation for ≥10 areas ( p  = 0.005) were predictors of RR. Conclusions: New predictive factors for recurrences of ASSC treated with IMRT have been found, suggesting that the delineation accuracy is essential for regional control.